SO2 gas adsorption on carbon nanomaterials: a comparative study - Babu, Deepu J.; Puthusseri, Divya; Kühl, Frank G.; Okeil, Sherif; Bruns, Michael; Hampe, Manfred; Schneider, Jörg J. (Beilstein Journal of Nanotechnology, 2018)
Owing to their high stability against corrosive gases, carbon-based adsorbents are preferentially used for the adsorptive removal of SO2. In the present study, SO2 adsorption on different carbon nanomaterials namely carbon nanohorns (CNHs), multiwalled carbon nanotubes (MWNTs), single-walled carbon nanotubes (SWNTs) and vertically aligned carbon nanotubes (VACNTs) are investigated and compared against the adsorption characteristics of activated carbon and graphene oxide (GO). A comprehensive overview of the adsorption behavior of this family of carbon adsorbents is given for the first time. The relative influence of surface area and functional groups on the SO2 adsorption characteristics is discussed. The isosteric heat of adsorption values are calculated to quantify the nature of the interaction between the SO2 molecule and the adsorbent. Most importantly, while chemisorption is found to dominate the adsorption behavior in activated carbon, SO2 adsorption on carbon nanomaterials occurs by a physisorption mechanism.
Keywords: adsorption; carbon nanohorns; carbon nanotubes; heat of adsorption; sulfur dioxide; vertically aligned carbon nanotubes